Fileogeografía de tres especies de Goodeidos endémicos del centro de México: Allotoca catarinae, A. diazi y A. meeki Cyprinodontiformes: Goodeidae) - Corona Santiago, Diushi Keri (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
Allotoca diazi, A. meeki and A. catarinae are Goodeidae family representatives, a group of fish endemic to central Mexico. Each of the three species are isolated in separate water bodies: Lake Patzcuaro, Lake Zirahuén and Cupatitzio subwatershed respectively. According to the situation of the distribution range, we would expect a genetic structure distinct from each other. However, these species are closely related genetically and morphologically and consequently, they are a group with high taxonomic and biogeographic complexity. The aim of this study is to determine the evolutionary history of the three species under the assumption that the current distribution is closely linked to the geological history of the region. Molecular markers were used with variable mutation rates (Cytochrome b and microsatellites) that have demonstrated their ability to solve intraspecific and individual level, respectively. 109 sequences were obtained mitochondrial Cytochrome b gene (Cytb 1140pb) and 96 genotypes of 7 microsatellite loci in three species. Were implemented for phylogenetic reconstruction, phylogeographic, level of genetic structure, historical demography analysis of species and prediction models of ecological niche in the past and future. Based on Cytb, genetic distances (0.3-0.6%) are lower than those reported among sister species of the family (1.7-11%). All populations of A. catarinae have one haplotype in 52 individuals, indicative of a founder effect or recurrent bottleneck. This species does not share any haplotype with the other two species. The other haplogroup is formed by A. diazi and A. meeki and not resolved as reciprocal monophyly, where A. diazi is the most diverse with five haplotypes in 35 individuals and shared two haplotypes with A. meeki. The latter only has 3 haplotypes in 22 individuals analyzed. The microsatellites showed a low level but significant genetic structure among species (Fst= 0.113). The highest genetic differentiation was found between A. catarinae respect to A. diazi and A. meeki (Fst=133 and Fst=109, respectively).

Allotoca diazi, A. meeki y A. catarinae son representantes de la familia Goodeidae, un grupo de peces endémicos del Centro de México. Cada una de las tres especies se encuentran aisladas en cuerpos de agua independientes: el Lago de Pátzcuaro, el lago de Zirahuén y la subcuenca del río Cupatitzio respectivamente. De acuerdo a la situación particular del rango de distribución, se esperaría una estructura genética bien diferenciada entre sí. Sin embargo estas especies se encuentran estrechamente relacionadas genética y morfológicamente y por consecuencia, son un grupo con alta complejidad taxonómica y biogeográfica. El objetivo de este estudio es determinar le historia evolutiva de las tres especies bajo la hipótesis de que su actual distribución está estrechamente vinculada a la historia geológica de la región. Se utilizaron marcadores moleculares con tasas de mutación variables (Citocromo b y Microsatélites) que han demostrado su capacidad de resolución intraespecífico y a nivel de individuo, respectivamente. Se obtuvieron 109 secuencias del gen mitocondrial Citocromo b (Cytb 1140pb) y 96 genotipos de 7 loci de microsatélites en las tres especies. Se implementaron análisis para la reconstrucción filogenética, filogeografica, nivel de estructura genética, de demografía histórica de las especies y modelos de predicción de nicho ecológico hacia el pasado y futuro. En base al Cytb, las distancias genéticas (0.3-0.6%) son menores que las reportadas entre especies hermanas de la familia (1.7-11%). Todas las poblaciones de A. catarinae tienen un único haplotipo en 52 individuos, indicativo de un efecto fundador o un cuello de botella recurrente. Esta especie no comparte ningún haplotipo con las otras dos. El otro haplogrupo está conformado por A. diazi y A. meeki y no se resuelve como monofilia recíproca, donde A. diazi es la más diversa con 5 haplotipos en 35 individuos y comparte dos haplotipos con A. meeki.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-M-2013-1014; Opción en ecología y conservación; Filogeografía; Especies; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1697